RACISM TOWARD THE BLACKS DURING THE AMERICAN CIVIL WAR AS DEPICTED IN EDGAR LAWRENCE DOCTOROW’S THE MARCH - CHOLIFAH, NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : racism, stereotype, prejudice, discrimination Slavery in the United States is closely connected to the American CivilWar between the North and the South which was happened in 1861-1865. Slavery deals with the ill-treatment of the Whites to the Blacks. Moreover, thosetreatments to the Blacks became the bad issues in illustrating the racism duringAmerican Civil War. Besides, the writer conducted a study by using sociologicalapproach about racism of critical race theory during the American Civil War.This study attempts to reveal the problem of how racism toward the Blacks during American Civil War is depicted in Doctorow’s The March novel. It is alsoassociated with the existence of stereotype, prejudice, and discrimination to the Blacks. Then, this study uses qualitative approach in order to observe and determine the data by the writer’s way of thinking.For the findings, the writer found the data in form of sentences as the evidences of racism to the Blacks. Besides, the writer separates racism in two perspectives to analyze the data, those are stereotype and prejudice, also discrimination. The most often points appeared in The March are discrimination perspective. While, stereotype and prejudice are the least appeared. Directly or indirectly, the Whites perform the racism attide through their negative stereotype and prejudice to the Blacks.